A novel phenotype of 13q12.3 microdeletion characterized by epilepsy in an Asian child: a case report - Mina Wang; Bin Li; Zehuan Liao; Yu Jia; Yuanbo Fu (BMC, 2020)
Abstract Background The microdeletion of chromosome 13 has been rarely reported. Here, we report a 14-year old Asian female with a de novo microdeletion on 13q12.3. Case presentation The child suffered mainly from two types of epileptic seizures: partial onset seizures and myoclonic seizures, accompanied with intellectual disability, developmental delay and minor dysmorphic features. The electroencephalogram disclosed slow waves in bilateral temporal, together with generalized spike-and-slow waves, multiple-spike-and-slow waves and slow waves in bilateral occipitotemporal regions. The exome sequencing showed no pathogenic genetic variation in the patient's DNA sample. While the single nucleotide polymorphism (SNP) array analysis revealed a de novo microdeletion spanning 2.324 Mb, within the cytogenetic band 13q12.3. Conclusions The epilepsy may be associated with the mutation of KATNAL1 gene or the deletion unmasking a recessive mutation on the other allele, and our findings could provide a phenotypic expansion.